Genome-wide analysis of bromodomain gene family in Arabidopsis and rice - Abiraami, T. V.; Sanyal, Ravi Prakash; Misra, Hari Sharan; Saini, Ajay (Frontiers in Plant Science, 2023)
The bromodomain-containing proteins (Brd-proteins) belongs to family of ‘epigenetic mark readers’, integral to epigenetic regulation. The Brd-members contain a conserved ‘bromodomain’ (BRD/BRD-fold: interacts with acetylated-lysine in histones), and several additional domains, making them structurally/functionally diverse. Like animals, plants also contain multiple Brd-homologs, however the extent of their diversity and impact of molecular events (genomic duplications, alternative splicing, AS) therein, is relatively less explored. The present genome-wide analysis of Brd-gene families of Arabidopsis thaliana and Oryza sativa showed extensive diversity in structure of genes/proteins, regulatory elements, expression pattern, domains/motifs, and the bromodomain (w.r.t. length, sequence, location) among the Brd-members. Orthology analysis identified thirteen ortholog groups (OGs), three paralog groups (PGs) and four singleton members (STs). While more than 40% Brd-genes were affected by genomic duplication events in both plants, AS-events affected 60% A. thaliana and 40% O. sativa genes. These molecular events affected various regions (promoters, untranslated regions, exons) of different Brd-members with potential impact on expression and/or structure-function characteristics. RNA-Seq data analysis indicated differences in tissue-specificity and stress response of Brd-members. Analysis by RT-qPCR revealed differential abundance and salt stress response of duplicate A. thaliana and O. sativa Brd-genes, and salinity-induced modulation of splicing pattern of one AtBrd gene, AtBrdPG1b. Bromodomain (BRD)-region based phylogenetic analysis placed the A. thaliana and O. sativa homologs into clusters/sub-clusters, mostly consistent with ortholog/paralog groups. The bromodomain-region displayed several conserved signatures in key BRD-fold elements (α-helices, loops), along with variations (1-20 sites) and indels among the Brd-duplicates. Homology modeling and superposition identified structural variations in BRD-folds of divergent and duplicate Brd-members, which might affect their interaction with the chromatin histones, and associated functions. The study also showed contribution of various duplication events in Brd-gene family expansion among diverse plants, including several monocot and dicot plant species.